Sistema COPPE-FORTRAN: um compilador Fortran Residente para o computador IBM-1130 - Salenbauch, Pedro (1972)
The overload of the universities' computing centers, due to the large number of new users that appeared with the Fortran teaching, is presented. The "COPPE-FORTRAN" System, a residente load and go Fortran compiler for the IBM-1130 computer is introduced as a solution. Various aspects of this system, as its objectives, components, implementation techniques and results are discussed.